CHARACTERISTICS OF DAIRY COW FARMERS AND FARM INCOME IN TWO AGROECOSYSTEMS - Kusmayadi, Tendy; Awaliyah, Fitri (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
Nowadays, the roles of dairy farm still become side business even though there are some people who already make it become main business. This study aims to examine the characteristics of farmers, income, revenue and cout ratio (R/C) of dairy farming in two different agroecosystems in Garut Regency. This study used the survey method. In total, there were 18 farmers in the dry land wetland agroecosystem (AES DL-Rainfed), and 95 farmers in the irrigated dryland agroecosystems (AES DL-IRF). Data were analyzed using the income formula, comparative analysis between revenues and cout s (R / C ratio). To test for differences in income and the R/C ratio, the student T-test was tested and explained descriptively. The results of a study conducted on dairy cow farmers at AES DL-Rainfed and AES DL-IRF in Garut Regency, it can be concluded that: farmers’ characteristics, age, and education at AES DL-Rainfed are good, while dairy cow farmers at AES DL-IRF are more experienced and results showed that the income of AES DL-Rainfed farmers had higher income than AES DL-IRF farmers. The ratio of business cout receipts shows that the dairy cow business in AES DL-IRF is more efficient than in (AES DL-Rainfed).